PENGEMBANGAN APLIKASI PENERJEMAH KATA MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC NET - KHAIRUNNISAAZZAHRA, KHAIRUNNISAAZZAHRA; FIQRIANSYAH, MUHAMMAD; IKANURHASANAH, IKANURHASANAH; KHUSNULADHA, KHUSNULADHA; GISKAYANANURZATLAH, GISKAYANANURZATLAH (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi Bisnis Riau, 2025)
This research aims to develop an efficient and user-friendly word translation application based on Visual Basic .NET 2010. This application is designed to support translation between English and Indonesian, focusing on speed and accuracy. By using a database-based word matching technique, the application provides fast translation results without requiring complex algorithms. Testing shows that this application produces accurate translations and has a user-friendly interface, making it accessible to users from various backgrounds. The results of this research contribute to the development of more efficient translation applications that are accessible to a wider audience.